PENERAPAN MODEL PEMBELAJARAN GUIDED INQUIRY UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR RASIONAL SISWA KELAS VIII-F SMP NEGERI 5 SURAKARTA TAHUN AJARAN 2011/2012 - Budiono, Eko; Dwiastuti, Sri; Probosari, Riezky Maya (P Biologi FKIP UNS Surakarta, 2012)
ABSTRACT ? Purpose of the researched is to improve the ability to rational thinkingh of through application of Guided Inquiry Strategies on all cognitive dimensions of VII F I Class Students SMP 5 Surakarta years 2011/2012. The research is an action research study Classroom what is done in several cycles. Each cycle consists of four stages: planning, action, observation and reflection. The research subjects are VIII-F Class Students SMP 5 Surakarta years 2011/2012. The data obtained by observation of written test. Techniques of data analysis using descriptive analysis technique. Validating data using triangulation research method. The research was motivated by the observation of the observations made on the VII-F class student of SMP 5 Surakarta. The results showed that the average achievement scores of rational thinking ability to process information on aspects on the 1st cycle by 56.15%, 69.73% in 2nd, and 70.68% in 3rd. Aspects of solving problems on 1st cycle by 38.22%, 67.83% in the second, 67.71%in 3rd . Aspects of a decision on the 1st cycle by 56.87%, 63.51% the second and 71% on 3rd.. The increase that occurs in every cycle showed that Guided Inquiry Learning model can improve the ability of rational thinking. Keywords: Guided Inquiry Learning Model, Rational Thinking, Cognitive Dimensions.